Revisiting Peripheral Osteoma of the Mandible with Case Series and Review of Literature - Soni, S. (Springer India, 2012)
Osteomas are benign lesions composed of mature compact and cancellous bone usually arising from craniofacial region. They can be central or peripheral, solitary or multiple. We are presenting few cases of giant peripheral osteoma’s of the mandible along with review literature of other jaw lesions with their diagnostic features and differential diagnosis. The purpose of presenting this paper is to evaluate radiopaque lesions of the jaw which require proper clinical and histological evaluation to reach a final diagnosis.